Cardiovascular diseases and complication in COVID-19 - Pavlović Siniša (University of Belgrade, Medical Faculty, 2021)
From the late fall of 2019 until the beginning of 2020, SARS-CoV-2 infection is becoming the biggest global challenge of health systems worldwide. Characteristic of the encounter with the disease caused by COVID-19 was a certain wandering in the mechanisms of action of the virus, its consequences, and thus in therapy. Various manifestations of the disease confirm the assumption that it is a systemic infection with the respiratory system as an entry route. We were also faced with the fact that the SARS-CoV-2 virus has great implications for the cardiovascular system. Patients with cardiovascular risk factors, including male gender, advanced age, diabetes, hypertension, and obesity, as well as patients with established cardiovascular and cerebrovascular disease, have been identified as particularly susceptible populations with increased morbidity and mortality from COVID-19. The effects on the cardiovascular system are reminiscent of other diseases caused by this group of viruses. There are biochemical, electrocardiographic and echocardiographic confirmations of functional disorders. It is basically an immune response caused by tissue inflammation, which results in prothrombogenicity as the dominant and biggest problem, coupled with the highest risk of a possible bad outcome. Being a systemic disease with numerous and different repercussions on the cardiovascular system, COVID-19 can lead to the appearance of all cardiovascular diseases that the patient did not have before, or to a significant worsening of the existing cardiovascular disease. The condition after the disease in most cases also means recovery, but great caution is needed due to possible time-distant complications. Since there is a high risk of death in the end, it is necessary to apply all available measures, especially in the field of prevention of thromboembolic complications, as a factor of the greatest risk of a bad outcome.